2018
DOI: 10.18542/ragros.v10i1.5212
|View full text |Cite
|
Sign up to set email alerts
|

Óleo Essencial De Erva-Cidreira Sobre Fitopatógenos De Espécies Florestais E Agrícolas

Abstract: Pertencente à família Verbenaceae, Lippia alba (Mill) N. E. Brown é amplamente utilizada na medicina popular devido suas propriedades analgésicas, calmantes e espasmolíticas. Neste trabalho, buscou-se avaliar o efeito do óleo essencial dessa espécie sobre o crescimento micelial de isolados de Fusarium spp. obtidos de Anacardium occidentale L. (caju); Zea mays L. (milho); Capsicum annuum L. (pimentão); Couratari oblongifolia Ducke & R. Knuth (tauari) e Rhizoctonia solani obtido da espécie Glycine max L. (so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The highest percentages of growth inhibition were observed in colonies submitted to industrialized oils, and there was a reduction of 28.9% and 5.7% for copaiba and castor beans, respectively [47]. The essential oil of Lippia alba (Mill) N. E. Brown showed a fungicidal effect from a concentration of 0.50 µL.mL -1 to a concentration of 1.25 µL.mL -1 for Rhizoctonia solani [48]. In this study, different results were observed for the products tested, with fungistatic effects on the growth of some phytopathogens as well as stimulation on the growth of others.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The highest percentages of growth inhibition were observed in colonies submitted to industrialized oils, and there was a reduction of 28.9% and 5.7% for copaiba and castor beans, respectively [47]. The essential oil of Lippia alba (Mill) N. E. Brown showed a fungicidal effect from a concentration of 0.50 µL.mL -1 to a concentration of 1.25 µL.mL -1 for Rhizoctonia solani [48]. In this study, different results were observed for the products tested, with fungistatic effects on the growth of some phytopathogens as well as stimulation on the growth of others.…”
Section: Resultsmentioning
confidence: 93%
“…obtained from different tree species. The highest percentages of growth inhibition were observed in colonies submitted to industrialized oils, and there was a reduction of 28.9% and 5.7% for copaiba and castor beans, respectively [47]. The essential oil of Lippia alba (Mill) N. E. Brown showed a fungicidal effect from a concentration of 0.50 µL.mL -1 to a concentration of 1.25 µL.mL -1 for Rhizoctonia solani [48].…”
Section: Resultsmentioning
confidence: 99%
“…The authors found a 91.1% inhibition on the fungus at concentrations of 1.0 and 1.5%. The effect may be related to the presence of the citronellar major component of the essential oil of C. citriodora, its antifungal effect being reported in the literature(OOTANI et al, 2016) Souza et al (2018). studied the essential oil of Lippia alba, whose major compound is Lcarvone, the same component present in the essential oil of M. spicata in the control of Fusarium spp.…”
mentioning
confidence: 99%